Loss of Linen Stock at Puri Bunda Mother and Child Hospital: What Affects This? - Drie, Ivan; Ratri, Devita Rahmani; Nuthea, Merry (Fakultas Kedokteran Universitas Brawijaya, 2021)
An insufficient number of linens, lack of linen cleanliness, and untimely linen provision will affect patient satisfaction, service quality, and hospital financing. Data at Puri Bunda Mother and Child Hospital Malang showed 108 linen loss incidents from the initial stock of 792 linens. This study was conducted to identify the factors that influence linen loss at Puri Bunda Mother and Child Hospital Malang. The root of the problems was identified through observations, interviews, and Focus Group Discussion (FGD) with the laundry staff, followed by analysis using a fishbone diagram and creating a Pareto diagram to select the main root of the problems. The study results indicate the absence of hospital policies that regulate the technical management of linen, weak evaluation monitoring, and inadequate linen management planning that contribute to the incidence of linen loss.